Performance Analysis on IEEE 802.11ah Standard with Enhanced Distributed Channel Access Mechanism - Oktaviana, Ana; Perdana, Doan; Negara, Ridha Muldina (CommIT (Communication and Information Technology) Journal, 2018)
IEEE 802.11ah is a new task group on the IEEE 802.11 standard designed to work on the 900 MHz. It is with a range of communication coverage up to 1kilometer, lower energy consumption, and up to 8191 stations. There are two types of STAs in 802.11ah: sensor type to support sensor service and non-sensor type for offload service. In this research, it only focuses on non-sensor STA. For non-sensor STA, maximizing throughput is more important than power consumption. This research aims to see the performance of IEEE 802.1 1ah with Enhanced Distributed Channel Access (EDCA). To achieve that purpose, a mechanism is needed to provide guarantees various services required by theSTA. EDCA is an access mechanism used to set the Quality of Service (QoS) for the IEEE 802.11 standard through modifications in MAC layer. In this research,it focuses on one of the EDCA parameters, Arbitration Inter-Frame Space (AIFS). In addition, this research also focuses on the 802.11ah feature is Restricted Access Window (RAW) by changing the number of the RAW groups. From the results of the research, it is found that the improvement scheme with Arbitration Inter-Frame Space Number (AIFSN) value AC BK = 2, AC BE = 1, AC VI = 1, AC VO = 1 has better performance compared to the default scheme with AIFSN value AC BK = 7, AC BE = 3, AC VI = 2, AC VO = 2) with an average throughput of 1.504598 Mbps, average overall delay of 0.066242 second and average PDR of 62%. In addition, changes in the number of RAW groups and RAW slots affect network performance. This feature can improve the value of throughput, average delay, and Packet Delivery Ratio. The goals of this research is to know the effect of AIFSN value changes on AIFSN parameters, variation of RAW group and RAW slot number to throughput,average delay and packet delivery ratio.